THE GROWTH OF PATIN Pangasiodon hypophthalmus IN A CLOSE SYSTEM TANK - Taufik Ahmad; Lilis Sofiarsih; Kusmana Kusmana (Indonesian Aquaculture Journal, 2007)
This experiment aimed to evaluate the possibility of using integrated recirculation production system for patin grow-out. Each of twelve concrete 2.5 m x 4.0 m x 1.0 m tanks filled to 0.73 m depth was stocked with 100 juvenile patin, 9-10g body weight. Six tanks were equipped with sand and palm (Arenga pinata) fibre filters planted with vegetables, lettuce and kangkoong. A submersible pump was installed in each tank to assure continuous water recirculation at the rate of 0.4 L sec-1. The filtered water flowed into the tank at the surface (SC treatment), or at the bottom (BC treatment). In the other 6 tanks, the water flowed continuously from a concrete canal in an open culture system at a similar rate and with similar water entrance positions (SO and BO treatments). The experiment was arranged in a completely randomized design with three replicates. The fish were fed dry pelleted feed to satiation and sampled every other week for growth observation. After 90 days, the average individual weight of the fish attained the range of 80-100 g. The fish grew significantly faster (P<0.05) in SC tanks compared to those in the rest of the tanks, except in BC tanks. Denser growth of plankton and more suitable water quality was considered to encourage faster growth of the fish in close system tanks. The survival of the fish was not significantly different (P>0.05) among treatment, ranging from 99% to 100%. In terms of water usage, the closed system tanks produced fish weighing 202.38–220.05 g m-3, much more efficiently than did the open system tanks, 1.87–1.89 g/m3. The vegetables, either lettuce or water spinach, grew well on the filter. These results suggest that the integrated recirculation tank system is suitable for patin culture.